One candidate method based on short-lived indicator for burnup analysis. (September 2018) - Zhao, Shangquan; Wang, Guanbo; Ma, Jimin; Dou, Haifeng; Li, Rundong; Zhang, Lei; Qian, Dazhi
Abstract: One novel gamma spectrometry method based on short-lived fission products was developed that can infer the level of burnup without complex computations or knowing irradiation history. The relationship between the burnup information and equilibrium concentration of short-lived indicators was derived. In addition, new candidate indicators for gamma spectrum analysis, such as 88 Kr, 91 Sr, 92 Sr, 135 I and 142 La were screened out. The results of three cases simulated with ORIGEN and MCNP were in good agreement with the theoretical values. Highlights: One burnup measurement method is proposed based on short-lived fission products. The key of this method is to make the nuclides reach an equilibrium concentration. New short-lived nuclides are screened out as indicators for burnup analysis. this method has a wider range of applications for burnup measurement.